Penguatan Implementasi Literasi Digital dalam Membangun Critical Thinking Guru di Era Revolusi Industri 4.0 - Muhamad Nazib, Fiqra; Masripah, Masripah; Nasrullah, Yufi Mohammad; Saifullah, Iman; Jamal, Ahmad; Firdaus, M (Pencerah, 2024)
The focus of this service is to build teachers' critical thinking in the era of industrial revolution 4.0 by strengthening the implementation of digital literacy at Asshiddiqiyah Middle School. The aim of the service is to find out the implementation, obstacles and solutions to the use of digital literacy by teachers in developing critical thinking in the era of revolution. The service method uses the following steps: (1) Preparation stage for literacy studies (field studies to find out the current conditions of Islamic boarding schools that have implemented modernization. Service team; (2) Implementation stage. There is assistance in implementing the digitalization of Islamic boarding schools by the service team by involving learning technology experts/experts.; (3) Evaluation Stage: In this stage, a final assessment is carried out in the evaluation and improvement of the mentoring that has been prepared. The population in this service is all 40 Asshiddiqiyah Middle School teachers, while the sampling used is the census technique, namely examining the research subjects thoroughly. The researcher did not carry out sampling, because the entire teacher population was used as respondents. The results of this service. The implementation of digital literacy at Asshiddiqiyah Middle School focuses on developing teachers' digital literacy skills, including wise use of the internet, information evaluation and online security. Teachers are encouraged to understand how to work with software, the internet and social media wisely, being able to evaluate the reliability of information found online. Become intelligent, critical and responsible users in facing an increasingly complex digital world.